Talking Comics with Nick Sousanis - Jason D. DeHart (University of Oklahoma Libraries, 2022)
In this Study & Scrutiny interview, Jason DeHart (Assistant Professor of Reading Education at Appalachian State) had the pleasure of discussing the comics medium with scholar and artist Nick Sousanis. Sousanis is the author of Unflattening, a dissertation that draws on the affordances of the graphic novel medium to explore the ontology of visual storytelling. Topics include salient titles, steps in making comics with university students, and the inspiration behind Sousanis's work.